The Making of Jose Garcia Villa's Footnote to Youth - Chua, Jonathan (Archīum Ateneo, 2024)
This article recounts the story behind the publication of Villa’s stories and his book Footnote to Youth: Tales of the Philippines and Others (1933) in the United States. First, the conditions of the American literary marketplace are briefly described. Second, documents pertaining to the realization in print of Villa’s stories and his book are analyzed as sites of negotiations between colonial subject (Villa) and the colonial master (his American editors and publishers). Finally, an account of how Villa was made to circulate in the Philippines after the publication of his stories and his book in the United States is given. From these discussions the article hopes to show that Villa’s self-fashioning by publication was both subject to and critical of the colonial condition, alternately reinforcing it and challenging it.